2021
DOI: 10.3390/v13071371
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assay for Profiling Anti-SARS-CoV-2 Antibodies and Their ACE2/Spike RBD Neutralization Capacity

Abstract: Serological assays have been widely employed during the coronavirus disease 2019 (COVID-19) pandemic to measure antibody responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and to track seroconversion in populations. However, currently available assays do not allow determination of neutralization capacity within the assay protocol. Furthermore, commercial serology assays have a high buy-in cost that is inaccessible for many research groups. We have replicated the serological enzyme-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Our observation was corroborated by repeating the measurements using the same IgG4-specific secondary antibody as well as by using the same clone from an alternative source (including differences in concentrations and storage buffers), which makes us confident that the results presented are valid. Moreover, we presented one of the most comprehensive cross-validations to date of all secondary antibodies -widely used in research on SARS-CoV-2 (Crowley et al, 2021;Fraley et al, 2021;Kim et al, 2021;Lee et al, 2021;Newell et al, 2021;Phelan et al, 2021;Pullen et al, 2021;Yates et al, 2021) and in other fields (Minassian et al, 2021;Sanchez Vargas et al, 2021;Tschismarov et al, 2021;Jennewein et al, 2022;Toney et al, 2022) -employed in this study and have confirmed their specificity to their target. We have noted that the sensitivity of the anti-human IgG1 antibody used can benefit from a higher concentration; however, it would come at a cost of compromising its specificity as the antibody shows cross-reactivity to other IgG subtypes at slightly increased concentrations, therefore, presenting a less favorable sensitivity-to-specificity profile than the other secondary antibodies.…”
Section: Discussionsupporting
confidence: 63%
“…Our observation was corroborated by repeating the measurements using the same IgG4-specific secondary antibody as well as by using the same clone from an alternative source (including differences in concentrations and storage buffers), which makes us confident that the results presented are valid. Moreover, we presented one of the most comprehensive cross-validations to date of all secondary antibodies -widely used in research on SARS-CoV-2 (Crowley et al, 2021;Fraley et al, 2021;Kim et al, 2021;Lee et al, 2021;Newell et al, 2021;Phelan et al, 2021;Pullen et al, 2021;Yates et al, 2021) and in other fields (Minassian et al, 2021;Sanchez Vargas et al, 2021;Tschismarov et al, 2021;Jennewein et al, 2022;Toney et al, 2022) -employed in this study and have confirmed their specificity to their target. We have noted that the sensitivity of the anti-human IgG1 antibody used can benefit from a higher concentration; however, it would come at a cost of compromising its specificity as the antibody shows cross-reactivity to other IgG subtypes at slightly increased concentrations, therefore, presenting a less favorable sensitivity-to-specificity profile than the other secondary antibodies.…”
Section: Discussionsupporting
confidence: 63%
“…A previously validated in-house neutralization assay was used to assess the ability of serum antibodies to neutralize the angiotensin-converting enzyme (ACE2) receptor-Spike RBD. 29 Plates were coated with recombinant RBD (aa319–541; Peak Proteins) in phosphate-buffered saline (PBS) and blocked with 3% milk powder in PBS-0.1%Tween (PBST). Serum samples were diluted 1:50 in 1% milk in PBST.…”
Section: Methodsmentioning
confidence: 99%
“…Results are presented as % neutralization in comparison with a pool of 6 pre-pandemic controls, with a lower percentage indicating greater neutralization capacity. 29 …”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, natural infection and vaccinations produced a polyclonal antibody response targeting several regions of the spike protein ( 22 ). Moreover, a recent study has shown that mRNA vaccine-induced spike protein-specific antibodies continue to drive Fc effector functions, suggesting a capacity for extra-neutralizing antibodies to contribute to disease control ( 23 ). Thus, it is likely that the current serologic testing could reflect the humoral response against COVID-19 well.…”
Section: Discussionmentioning
confidence: 99%